Cultural Shifts: A Longitudinal Study of the Changing Reading Practices of Thai Graduate Students at an Australian University - Bell, Joyce (The Reading Matrix, 2005)
Cultural shifts: A longitudinal study of the changing reading practices of Thai postgraduate students at an Australian university.Abstract The importance of reading for academic study cannot be overemphasised. At the postgraduate level, in particular, students are faced with complex text interpretation processes. International students, in addition, have to make a significant cultural/study shift; not only do they have to become accustomed to the reading of academic texts using discipline-specific discourse patterns but often have to adjust to the different conventions used by authors from cultural backgrounds other than their own.Despite the difficulties which international postgraduate students experience, reading problems and the expected outcomes have been cited as one of the most neglected areas of research (Smith 1998). In addition, little is know about international student reading practices and how they change during study at an Australian university.This paper presents part of a longitudinal study which used metacognitive and framing theories to explore the adjustments and self awareness of adjustment when reading in English by Thai and Indian postgraduate students. The data presented here from Thai postgraduate students reveal significant changes in reading practices between first and third semester and the students? awareness of these changes. The research has implications for postgraduate supervision and curriculum development at the postgraduate level.